KLASIFIKASI KESALAHAN SISTAKSIS ESSAY TUGAS AKHIR MAHASISWA AKADEMI BAHASA ASING BOROBUDUR JAKARTA - Nugraheni, Wiwik Sari Dewi (Lembaga Layanan Pendidikan Tinggi Wilayah III Jakarta, 2014)
Abstract: Writing ability is one of the most important skills as called the highest achievement in learning english properly. Sometimes there are lots of sintaksis error that is the words arrangement in a sentence in essay writing. The purpose of this research is to find out the clarification of the sintaksis errors in essay writing. The method used qualitative and description approach of the error analysis. The population is all of the students of Foreign Language Academy (ABA Borobudur, Jakarta) who took the Essay Writing subject. The results showed that the clarification of the sintaksis error as follows: (1) The most grammatical error is Subject/Verb Agreement; it’s about 35%, (2) Verb Tense; 23,3%, (3) Word Choice; 16,7%: (a) Spelling and Capitalization for each of it 8,3%, (b) Singular/Plural Noun 3% and the last (c) Word Order 3,4%. It is recommended to students to pay attention in essay writing properly especially to the grammatical errors that have been recognized.